IMPLEMENTASI PEMBELAJARAN INKLUSIF DI SEKOLAH DASAR WILAYAH PULAU-PULAU KECIL PERBATASAN: TANTANGAN DAN STRATEGI ADAPTASI GURU - Rumtutuly, Fransheine; Souhoka, Renny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of inclusive learning in elementary schools located in small border islands and to identify the challenges and adaptive strategies employed by teachers in addressing limited resources and complex geographical conditions. The research adopts a qualitative approach using the narrative inquiry method, conducted at SD Negeri Tiakur, Moa District, Southwest Maluku Regency. Data were collected through in-depth interviews, classroom observations, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that inclusive learning has been implemented despite numerous constraints, such as limited pedagogical competence in inclusive education, the absence of special education teachers (GPK), and inadequate learning facilities and training opportunities. Nevertheless, teachers demonstrated a strong commitment by applying flexible, contextual, and collaborative adaptation strategies—such as utilizing local resources, implementing simple project-based learning, and fostering an empathetic and supportive classroom environment. The key success factors for inclusive practices in border areas lie in teachers’ creativity, humanistic values, and adaptive capacity. This study recommends strengthening inclusive education policies through continuous professional development, the recruitment of special education assistants, and enhanced collaboration among schools, local governments, and communities to ensure equitable and sustainable education for all children across Indonesia.